MYTHIC MEMORY AND RITUAL PRACTICE: READING BALINESE HINDU LITERATURE AS LIVING THEOLOGY - I Wayan Mandra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Balinese Hindu literature embodies a living theology where myth and ritual intersect as continuous acts of remembrance. Rather than static mythic texts, Balinese Hindu literature serves as a dynamic field in which theological principles are narrated, embodied, and performed. This study explores how selected Balinese texts—such as Kakawin Arjunawiwaha, Geguritan Dharma Prawerti, and Kidung Wargasari—function as vehicles of mythic memory that sustain ritual practice and spiritual identity. Through qualitative literary and ethnographic analysis, the paper demonstrates that these works preserve myth not merely as narrative heritage but as a sacred performative discourse that shapes the religious consciousness of Balinese society. The findings affirm that Hindu literature in Bali is a living theology: a poetic body where divine principles, ritual gestures, and ethical transformation converge.